EFEKTIFITAS PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT ( PPKM ) BAGI USAHA KECIL MASYARAKAT DI KELURAHAN MALALAYANG SATU TIMUR KECAMATAN MALALAYANG KOTA MANADO - KEZIA LOUISA MOGOT; FEMMY TULUSAN; VERY LONDA (Sam Ratulangi University, 2023)
In Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises, it is stated that MSMEs are business activities that are able to expand employment opportunities and are able to provide broad economic services to the community, and can play a role in the process of equitable distribution and increase in people's income, encouraging economic growth. , and play a role in realizing national stability. However, from observations in the field, the researchers found several problems, namely they were still operating past the time limit that had been set, namely at 21.00 WITA to 00.00 WITA, Warung the process approach, the goal approach. approaches). This study uses a qualitative method. There were 15 informants in this study. Data collection techniques used are interviews. However, in reality, small and medium enterprises still feel the impact of the imposition of restrictions on community activities, namely the community suffers losses or decreases in income, the government must find other solutions in an effort to provide stimulation for business actors other than providing capital (BPUM). related or looking for a solution so that (PPKM) does not have a bad impact on small business actors in the malalayang one east village. So that nothing bad happens for business actors or goes bankrupt due to a decrease in business income resulting in reduced operating hours of business premises and restrictions on the number of customers or customers in a place of business even though they have implemented health protocols so that income is less stable for small business actors in Malalayang Village. One East. Keywords: Effectiveness, Small Business, Community